2014
DOI: 10.1021/es503005m
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and Biotransformation Potential of Veterinary Ionophore Antibiotics under Different Redox Conditions

Abstract: Veterinary ionophore antibiotics (IPAs) are polyether compounds used extensively in the livestock industry to promote animal growth and prevent coccidia infection. However, the environmental fate and impact of IPAs are not fully understood. In this study, the inhibition and biotransformation potential of the most commonly used IPAs, monensin (MON) and salinomycin (SAL), were investigated under well-defined aerobic, nitrate-reducing, fermentative/sulfate-reducing, and fermentative/methanogenic conditions. Batch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…While these results cannot be 290 verified from the data, they again demonstrate that screened and unscreened samples behave 291 similarly, and clearly show that aerated samples benefit from much faster monensin degradation. 292 This is similar to observations of monensin biotransformation in mixed cultures derived from 293 poultry litter and litter-amended soil, which demonstrated much faster transformation under 294 aerobic versus anoxic conditions (Sun et al, 2014). In addition to aeration resulting in shorter 295 half-lives, the potential for difference in reaction order (zero-versus first-order) will affect how 296 monensin degrades in each system.…”
Section: Aeration On Monensin Dissipation 265supporting
confidence: 70%
See 2 more Smart Citations
“…While these results cannot be 290 verified from the data, they again demonstrate that screened and unscreened samples behave 291 similarly, and clearly show that aerated samples benefit from much faster monensin degradation. 292 This is similar to observations of monensin biotransformation in mixed cultures derived from 293 poultry litter and litter-amended soil, which demonstrated much faster transformation under 294 aerobic versus anoxic conditions (Sun et al, 2014). In addition to aeration resulting in shorter 295 half-lives, the potential for difference in reaction order (zero-versus first-order) will affect how 296 monensin degrades in each system.…”
Section: Aeration On Monensin Dissipation 265supporting
confidence: 70%
“…S2). The high pH of the aerated 273 samples indicates that hydrolysis is not a transformation pathway (Sun et al, 2014). The 274 13 decrease in DOC ( Fig.…”
Section: Aeration On Monensin Dissipation 265mentioning
confidence: 97%
See 1 more Smart Citation
“…However, most of the studies focused on the degradation kinetics of MON and only to a lesser extent on the identification of TPs. A few studies investigated oxidative TPs, namely the conversion of MON with metalloporphyrins [28], the Jacobson catalyst [29] and the inhibition and biotransformation under different redox conditions [30].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies and on-farm experiences have shown a decrease in methane production upon the first introduction of monensin or monensin-laden manure to anaerobic digesters ( 9 12 ). These studies indicated that monensin indirectly inhibits methanogenesis by depleting the precursor acetate.…”
Section: Introductionmentioning
confidence: 99%